Correction: Coppieters de Gibson, L.; Garner, P.N. Training a Filter-Based Model of the Cochlea in the Context of Pre-Trained Acoustic Models. Acoustics 2024, 6, 470–488 - Louise Coppieters de Gibson; Philip N. Garner (Acoustics)
The authors would like to make the following corrections to the original publication [...]